Combining Chemical Functionalization and FinFET Geometry for Field Effect Sensors as Accessible Technology to Optimize pH Sensing - Dipti Rani; Serena Rollo; Wouter Olthuis; Sivashankar Krishnamoorthy; César Pascual García (Chemosensors, 2021)
Field Effect Transistors (FETs) have led the progress of applications measuring the acidity in aqueous solutions thanks to their accuracy, ease of miniaturization and capacity of multiplexing. The signal-to-noise ratio and linearity of the sensors are two of the most relevant figures of merit that can facilitate the improvements of these devices. In this work we present the functionalization with aminopropyltriethoxysilane (APTES) of a promising new FET design consisting of a high height-to-width aspect ratio with an efficient 2D gating architecture that improves both factors. We measured the transistor transfer and output characteristics before and after APTES functionalization, obtaining an improved sensitivity and linearity in both responses. We also compared the experimental results with a site-biding model of the surface buffering capacity of the APTES functionalized layers.